Radiation Measurement at X-Ray Centres of a few Hospitals in Kathmandu City, Nepal - Giri, Karan; Giri, Dhiraj; Murthy, V Krishna (Kathmandu University Journal of Science, Engineering and Technology, 2010)
The ionizing radiation has hazardous health effects upon human exposure. Different types of cancers are reported to be arising on account of overt exposure to ionizing radiation like X-rays. This study reports occupational exposure as well as general exposure to the public and persons visiting radiology department in hospitals of Kathmandu city for diagnostic and therapeutic purposes. A portable environment radiation monitor was used to quantify the total radiation in places of work in the X-ray departments of 13 hospitals located in different parts of city. The findings show increased exposure and in some instances very high levels of unintentional exposure to radiation. DOI: 10.3126/kuset.v3i2.2895 Kathmandu University Journal of Science, Engineering and Technology Vol.3, No.2, August 2007, pp 31-34